Evaluating privacy attacks in named data network - Dogruluk, Ertugrul (2016)
The main usage pattern of the Internet is changing from end-to-end communication to content distribution and access. To support this change, the actual Internet has several add-on as Content Delivery Networks (CDNs) and Web caches.To have a native support architecture for content distribution, clean state information-centric networking is being proposed for Future Internet. The Named Data Network (NDN) is one of the most promising information-centric networking architecture. The in-network storage (aka caches) capability of ICNs and content name visibility bring more efficiency and lower traffic to the network for content distribution.However, the human-readable naming and in-network storage of data increase the opportunity and possible victims of cache privacy attacks. The most used attack type is called timing attack.Based on the hypothesis that almost all timing attacks are detectable, this work proposes a mechanism for turning on a random cache delay model only when a cache privacy attack is detected. Otherwise, there is not any additional delay. The rationale of this approach is to establish a tradeoff between the network efficiency and cache privacy guarantee. In comparison with other works proposed in the literature, the network efficiency is less affected.